2019
DOI: 10.1101/2019.12.19.882290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local sleep-like cortical reactivity in the awake brain after focal injury

Abstract: One Sentence Summary: Focal cortical injuries are associated with local intrusion of sleep-like dynamics over the perilesional areas which disrupt local signal complexity and coexist with typical wakefulness cortical reactivity patterns within the same brain. AbstractThe functional consequences of brain injury are known to depend on neuronal alterations extending beyond the area of structural damage. Although a lateralized EEG slowing over the injured hemisphere was known since the early days of clinical neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Recent work has shown that the balance between global SOs and local slow waves-delta waves (d)-determines whether there is an enhancement of skill or, instead, forgetting (Kim et al, 2019). Intriguingly, recordings in stroke patients (Poryazova et al, 2015;Sarasso et al, 2020;Tu-Chan et al, 2017;van Dellen et al, 2013) and in animal models of stroke (Burns, 1951;Burns and Webb, 1979;Carmichael and Chesselet, 2002;Gulati et al, 2015;Nita et al, 2007) have found a prevalence of local low-frequency power (<4 Hz) during awake periods; this also appears to be far more common after a cortical than a subcortical lesion (Macdonell et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the balance between global SOs and local slow waves-delta waves (d)-determines whether there is an enhancement of skill or, instead, forgetting (Kim et al, 2019). Intriguingly, recordings in stroke patients (Poryazova et al, 2015;Sarasso et al, 2020;Tu-Chan et al, 2017;van Dellen et al, 2013) and in animal models of stroke (Burns, 1951;Burns and Webb, 1979;Carmichael and Chesselet, 2002;Gulati et al, 2015;Nita et al, 2007) have found a prevalence of local low-frequency power (<4 Hz) during awake periods; this also appears to be far more common after a cortical than a subcortical lesion (Macdonell et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Future approaches should seek relationships and convergence between metrics derived from information theory, graph theory, and dynamical systems theory and strive to connect them with structural measures. Contemporary examples include the recent link found between PCI and subcortical atrophy [76] and the recent association between focal cortical lesions and the generation of pathological slow waves, disconnection, and lost complexity [77,78].…”
Section: Box 2 Whole-brain Computational Modelsmentioning
confidence: 99%
“…This could be further enhanced through comparison with results from sleep and anesthesia research, in which microscopic mechanisms have been more comprehensively probed in preclinical work [87], producing mechanistic frameworks that span from whole-brain phenomena, such as individual susceptibility, to anesthetic-state transitions (neural inertia), all the way to genetic susceptibility factors for anesthesia [38,88,89]. Indeed, work in rodents and cortical slices alike has recently demonstrated that neuronal "off " periods determine a dramatic collapse of large-scale interactions and complexity during non-REM sleep and anesthesia [90][91][92], which can also be assessed by using EEG coupled with TMS in humans with brain damage [77,78].…”
Section: Linking Micro-and Macroscalesmentioning
confidence: 99%
“…Although our sham stimulation produced a tactile vibratory sensation, somatosensory co‐stimulation was not completely controlled for in sham blocks. However, somatosensory co‐stimulation does not contribute significantly to the early TEPs considered in the present study 48,71 . Because we did not use individual MRI neuronavigation, variability in pre‐SMA and SMA‐proper locations may have confounded TEP results due to distinctive functional changes occurring in the pre‐SMA and SMA‐proper in PD 64 .…”
Section: Discussionmentioning
confidence: 76%